"A window into shock, pain, and attempted recovery": A decade of blogging as a coping strategy in New Orleans. (March 2018) - Watson, Brendan R
Interviews with bloggers examine the ongoing use of blogs to cope with the persistent community stress New Orleans has experienced post-Hurricane Katrina. Previously, the field of media studies has overlooked blogs' coping role. Cyber psychology has explored blogs' role in individual and emotional coping, but not task-oriented efforts to ameliorate sources of community stress. Among other insights, the unique intersection of media studies and cyber psychology explored in this study illuminates the double-edged sword that is the imagined audience. While a positive source of social support, efforts to attract and maintain an audience can impose the perceived pressure to "keep face" and maintain an angry blogging persona beyond its useful cathartic value. Combining perspectives from cyber psychology and media studies, this study contributes a more multifaceted understanding of how residents may use social media to cope with individual and community stress than has been explored in previous research.